Relevansi Pemikiran Ekonomi Ibnu Khaldun dalam Konteks Ekonomi Modern - Zuya, Devi Fitri; Aini, Nurul; Br Nasution, Marsya Pratiwi; Nabila, Nur Afiqah; Harza, M. Khadafi; Hayati , Fitri (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Ibn Khaldun is recognized as a prominent Muslim thinker who made significant contributions to the fields of economics, sociology, and politics. In his seminal work Muqaddimah, he introduced economic ideas that were far ahead of his time, including the concepts of national wealth, wage theory, market mechanisms, and the role of the state in fiscal policy. This study aims to examine the core economic thoughts of Ibn Khaldun and their relevance to current economic dynamics. Using a qualitative descriptive approach based on literature review, the study finds that many of Khaldun's ideas remain highly relevant, particularly regarding the importance of productivity, fiscal justice, and the integration of social and economic aspects in building a sustainable system. Most people know that Ibn Khaldun is one of the most famous Muslim thinkers, and he did a lot in the fields of politics, economics, and sociology.  In his monumental work, Muqaddimah discusses various long-established economic concepts, such as the market mechanism, wage theory, national wealth, and the role of the state in fiscal policy.  The purpose of this research is to study Ibn Khaldun's ideas on economics and evaluate how these impact contemporary economic developments.  The study found that many of Khaldun's ideas are still relevant today thanks to the use of descriptive qualitative methodology based on literature study. A sustainable and inclusive economic system relies on the idea of productivity as the source of economic growth, fiscal justice in the taxation system, and integration between social and economic aspects.  The results show that classical economic thought not only has historical value, but also offers solutions to many modern economic problems such as inequality, productivity stagnation, and institutional crisis.